Identifikasi Kandungan Asam Salisilat dalam Produk Krim Anti Jerawat di Pasar Tajinan Kabupaten Malang - Fendi Yoga Wardana; Nurul Fadila; Mayang Aditya Ayuning Siwi (LPPMKI - AKAFARMA AKFAR PIM, 2022)
Anti-acne cream is a type of cosmetics that is often used for skin care. Salicylic acid is often used as the active substance in this anti-acne cream. According to the Indonesian National Food and Drug Agency in 2019 on cosmetics, salicylic acid is allowed in cosmetics if it is not more than 2%. In this study, 6 types of anti-acne cream, from Tajinan Market, Malang Regency, were tested with the aim of studying the content of salicylic acid in anti-acne cream products. The test was performed qualitatively using a colour test with FeCl3 reagent (a positive reaction show a purple colour) and a thin layer chromatography (TLC) method using a solvent mixture of ethyl acetate;methanol;ammonia (8:1.90:0.10) as the mobile phase. Quantitative determination of the content was performed using UV-Vis spectrophotometry. The qualitative test with the colour test indicates that samples A and E are positive for containing salicylic acid. The results of the thin layer chromatography (TLC) test indicates that sample A is positive for containing salicylic acid with an Rf value of 0.66, which is the same as the comparison standard. The quantitative test with UV-Vis spectrophotometry indicates that the salicylic acid content in sample A is 2.516%, sample D is 1,400%, and sample E is 1.646%. In conclusion, only cream of sample A do not meet the requirements of the Indonesian National Food and Drug Agency because it has a salicylic acid content of more than 2%.